Iridium (III) photosensitisers for photoredox catalysed carboxylation reactions of ketimines - Davids, Tara (Department of Chemistry, 2025)
The increasing need for catalytic systems driven by sustainable energy sources continues to motivate the development of processes that utilise photochemical energy to initiate chemical reactions. Photoredox catalysis has piqued great interest in this regard, creating a means for a milder energy source (visible light) to drive chemical reactions and thus revolutionising the field of synthetic radical chemistry and photochemistry. Recently, photoredox catalysis has paved a way for the direct incorporation of CO2 into organic molecules, as a strategy to mitigate CO2 accumulation. Pertinent to this study, is the photoredox catalysed fixation of CO2 to afford unnatural -amino acids, which have important applications in the pharmaceutical industry. Following on from the above, polymetallic transition metal complexes have been promulgated as photocatalysts in processes such as CO2 reduction. These polymetallic photocatalysts were reported to exhibit higher reactivity due to multiple active sites, improved photostability and increased durability in comparison to their mononuclear congeners. We have also demonstrated enhanced photocatalytic abilities of trinuclear heteroleptic ruthenium(II) polypyridyl photocatalysts in the context of the visible light mediated regioselective hydrothiolation reaction of alkenes. The higher yields obtained for the hydrothiolation reaction was attributed to there being a greater driving force for electron transfer processes with the trinuclear complexes. In this study, a series of 2,2'-pyridyl substituted benzimidazole ligands (L1-L3) were synthesised via standard N-alkylation reactions. Subsequently, two mononuclear cationic bis-cyclometalated iridium(III) complexes (C1, C2) and a new trinuclear iridium(III) complex (C3) were synthesised. The complexes (C1-C3) were obtained as racemic mixtures (Λ, Δ isomers) which is an attribute of the helical chirality, inherent to these types of tris-bidentate octahedral complexes. Characterisation of the synthesised ligands and complexes was achieved by 1H NMR, 13C{1H} NMR spectroscopy, infrared spectroscopy and high-resolution mass spectrometry. A crystal structure was also obtained for the new iridium(III) complex (C2), and confirms its molecular structure. 2 Furthermore, the photophysical properties (absorption and emission studies), electrochemical properties, as well as the photostability of the synthesised iridium(III) complexes have been ascertained, where the effects of ligand modifications on these properties have been observed and described. Finally, the catalytic activity of complexes (C1-C3) was evaluated in the visible light mediated photoredox catalysed carboxylation reaction of ketimines using CO2, affording unnatural amino acids. This known reaction was selected as an ideal proof-of-concept reaction, due to the green nature of the reaction (with respect to Green Chemistry principles) and the utility of the -amino acid product. The desired amino acid salt product and/or an additional product was obtained in the photocatalytic reactions with complexes (C1-C3) as the photoredox catalysts. The structure of this additional product was elucidated via spectroscopic analysis. Differences in the photocatalytic activity exhibited by the synthesised iridium complexes (C1-C3) and the model photoredox catalyst, [Ir(ppy)2(dtbbpy)]PF6 is discussed herein. The results obtained from the photocatalysis highlight the importance of judicious ligand design when developing efficient and versatile photosensitisers, and reveal that the benzimidazole scaffold may not be the most well-suited N^N ligand for this application.